Development and validation of an LC-MS/MS method for the determination of six gestagens in kidney fats - Rejtharová, Martina; Rejthar, Libor (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2013)
A method for the determination of residues of six steroids with gestagenic action (altrenogest, medroxyprogesterone acetate, megestrol acetate, melengestrol acetate, acetoxyprogesterone and chlormadinone acetate) in animal fat tissue was developed. The procedure consists of methanol extraction, clean-up on an alumina column and LC-MS/MS measurement. The method has been validated according to Decision 2002/657/EC. Decision limits for all analytes were observed within the range from 0.3 to 1.7 ng g(-1), and recoveries were between 80% and 105%. The method is robust and can be applied for both screening and confirmatory analyses in routine residue monitoring.
Keywords: reprodukovatelnost výsledků; progestiny; ledviny; tuková tkáň; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Progestins; Animals; Kidney; chromatografie kapalinová; Tandem Mass Spectrometry; Reproducibility of Results; zvířata; Adipose Tissue